Adult weight change and premenopausal breast cancer risk: A prospective pooled analysis of data from 628, 463 women. Issue 5 (15th February 2020) - Schoemaker, Minouk J.; Nichols, Hazel B.; Wright, Lauren B.; Brook, Mark N.; Jones, Michael E.; O'Brien, Katie M.; Adami, Hans‐Olov; Baglietto, Laura; Bernstein, Leslie; Bertrand, Kimberly A.; Boutron‐Ruault, Marie‐Christine; Chen, Yu; et al.
Abstract : Early‐adulthood body size is strongly inversely associated with risk of premenopausal breast cancer. It is unclear whether subsequent changes in weight affect risk. We pooled individual‐level data from 17 prospective studies to investigate the association of weight change with premenopausal breast cancer risk, considering strata of initial weight, timing of weight change, other breast cancer risk factors and breast cancer subtype. Hazard ratios (HR) and 95% confidence intervals (CI) were obtained using Cox regression. Among 628, 463 women, 10, 886 were diagnosed with breast cancer before menopause. Models adjusted for initial weight at ages 18–24 years and other breast cancer risk factors showed that weight gain from ages 18–24 to 35–44 or to 45–54 years was inversely associated with breast cancer overall (e.g., HR per 5 kg to ages 45–54: 0.96, 95% CI: 0.95–0.98) and with oestrogen‐receptor(ER)‐positive breast cancer (HR per 5 kg to ages 45–54: 0.96, 95% CI: 0.94–0.98). Weight gain from ages 25–34 was inversely associated with ER‐positive breast cancer only and weight gain from ages 35–44 was not associated with risk. None of these weight gains were associated with ER‐negative breast cancer. Weight loss was not consistently associated with overall or ER‐specific risk after adjusting for initial weight. Weight increase from early‐adulthood to ages 45–54 years is associated with a reduced premenopausal breast cancer risk independently of early‐adulthood weight. Biological explanations are needed to account for these two separate factors. Abstract : What's new? Body weight in childhood and early adulthood plays a key role in determining premenopausal breast cancer risk but little is conclusively known about how subsequent weight changes affect this risk. Here the authors pooled results from existing studies on weight changes and breast cancer risk including more than 600, 000 premenopausal women. The results show that weight gain >10–15 kg from early adulthood on lowers the risk of developing premenopausal breast cancer, providing further evidence of body weight as an important determinant of breast cancer risk.